2020
DOI: 10.1128/aem.00305-20
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences of the Microbiota on the Life Span of Drosophila melanogaster

Abstract: To better understand how associated microorganisms (“microbiota”) influence organismal aging, we focused on the model organism Drosophila melanogaster. We conducted a metagenome-wide association (MGWA) as a screen to identify bacterial genes associated with variation in the D. melanogaster life span. The results of the MGWA predicted that bacterial cysteine and methionine metabolism genes influence fruit fly longevity. A mutant analysis, in which flies were inoculated with Escherichia coli strains bearing muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…In addition to locomotor activity, we examined here the influence of the microbiome of circadian rhythmicity, failing to detect an effect even when flies carried the hypomorphic per L allele. Finally, and in agreement with Selkrig et al 2018 In general terms, the several among-study discrepancies in microbiome effects on locomotor activity of Drosophila can be attributed, at least partly, to the differences in host genotype and diet, both of which are known to influence microbiome effects on host traits in Drosophila (Consuegra et al, 2020;Dobson et al, 2015;Jehrke et al, 2018;Keebaugh et al, 2019;Matthews et al, 2020;Wong et al, 2014) and other animals (Ezra-Nevo et al, 2020;Leigh and Morris, 2020). Two further issues relate specifically to this study.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to locomotor activity, we examined here the influence of the microbiome of circadian rhythmicity, failing to detect an effect even when flies carried the hypomorphic per L allele. Finally, and in agreement with Selkrig et al 2018 In general terms, the several among-study discrepancies in microbiome effects on locomotor activity of Drosophila can be attributed, at least partly, to the differences in host genotype and diet, both of which are known to influence microbiome effects on host traits in Drosophila (Consuegra et al, 2020;Dobson et al, 2015;Jehrke et al, 2018;Keebaugh et al, 2019;Matthews et al, 2020;Wong et al, 2014) and other animals (Ezra-Nevo et al, 2020;Leigh and Morris, 2020). Two further issues relate specifically to this study.…”
Section: Discussionsupporting
confidence: 88%
“…Microbiome-mediated alterations in metabolites in the host can lead to different survival outcomes. A recent study demonstrated that bacteria which lowered methionine content of food extended Drosophila host lifespan [108]. Although this was tested in flies, methionine acts as a larvicide against several mosquito species such as An.…”
Section: Adult Nutrition and Fitnessmentioning
confidence: 99%
“…[15,18,52,77,78]. In particular, in D. melanogaster evidence for the importance of variation between closely related bacteria is accumulating for life history of the host [26,29,[47][48][49][50][51]79].…”
Section: Variation Between Closely Related Microbes Is Important For mentioning
confidence: 99%
“…Techniques for the generation of gnotobiotic flies are readily available and standardized measurements of phenotypes exist. Affected phenotypes include the life history traits development time, fecundity, and life span as well as size of the adults [14,[26][27][28][29][30][31][32][33]. These traits are directly related to fitness, emphasizing the potential importance of microbes in host evolution and adaptation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation